Implementation of Continued Quality Improvement Through Strengthening Planning, Control, Leadership and Commitment In Improving Quality Performance and Its Impact On Quality Culture - Sururi Sururi; Nugraha Suharto; Aam Muamar; Yoki Ariyana; Siti Nurlatifah (LPPM Universitas PGRI Sumatera Barat, 2023)
The research aims to provide information about the Implementation of Continues Quality Improvement through Strengthening Planning, Control, Leadership, and Commitment in Improving Quality Performance and Its Impact on Quality Culture. This study uses a descriptive method with a quantitative approach. Data analysis was used in this study Path Analysis with data processing using SEM (Structural Equation Modeling). Descriptive method is used to describe the results of the model implementation. The population in this study were all private junior high school principals and teachers in Bandung Regency. The data collection technique uses a questionnaire, and measurements with a Likert scale range 1-5 for the six variables to be studied namely, strengthening planning, control, leadership, commitment, quality performance and quality culture. Based on the research results it is known that Quality Planning, Quality Control, Quality Leadership, and Quality Commitment through the mediation of Quality Performance each indirectly does not significantly influence Quality Culture. This is indicated by a significant p-value, namely p-value > 0.05. The path coefficient values (original sample) obtained are 0.042, 0.130, 0.136 and 0.036 respectively.